Catalytic hydroconversion of an organic waster oil to cyclanes over Ni/SiO2. (1st January 2023) - Li, Li; Wei, Xian-Yong; Shao, Chang-Wang; Li, Zhuang; Li, Jia-Hao; Fan, Zi-Chun; Lu, Kun-Lang; Liu, Fang-Jing; Kong, Qian-Qian; Zhao, Ji; Liu, Zhong-Qiu; Zong, Zhi-Min
Graphical abstract: Highlights: Ni/SiO2 is active for catalytically hydroconverting an organic waster oil (OWO). The catalytic hydroconversion includes hydrogenation and hydrodeoxygenation. All the organic species in the OWO were converted to cyclanes over Ni/SiO2 . The cyclanes have higher heat value of 28.52 MJ kg −1 than the OWO (37.04 MJ kg −1 ). Abstract: An organic waster oil (OWO) was ultrasonically extracted with isometric acetone/carbon disulfide mixed solvent at room temperature to obtain extractable portion (EP) with the yield of 99.1%. Ni/SiO2 was prepared by a deposition–precipitation method. EP consist of arenes (34.1%), oxygen-containing organic compounds (OCOCs, 62.4%), and nitrogen-containing aromatics (NCAs, 3.5%) determined with a gas chromatograph/mass spectrometer (GC/MS). It was subjected to catalytic hydroconversion (CHC) over Ni/SiO2 in n -hexane under initial hydrogen pressure (IHP) of 4 MPa at 220 °C for different periods of time to obtain catalytically hydroconverted EPs (CHCEPs). All the organic species detected in EP were completely converted into cyclanes in CHCEP6 and the heat value increased from 28.52 to 37.04 MJ kg −1 by the CHC. In Ni/SiO2, highly dispersed nickel nanoparticles and mesoporous support with suitable acid sites play significant roles in hydrogenating aromatic rings and removing heteroatoms, respectively. To understand the mechanism for the CHC of EP, the catalytic activity of Ni/SiO2 was investigated using 4-cumylphenol (CP) and 1, 3, 5-triphenylbenzene (TPB) as the OWO-related model compounds. As a result, CP and TPB were completely converted over Ni/SiO2 in n -hexane at 220 °C or 200 °C under 4 MPa of IHP for 2 h, proving that Ni/SiO2 exhibits favorable CHC reactivity under mild conditions. Moreover, Ni/SiO2 has excellent cyclability after 4 runs and can be recovered by reduction with H2 at 500 °C for 4 h.